PENGARUH RASKIN TERHADAP PENGELUARAN KONSUMSI DAN SOSIAL EKONOMI SERTA KESEJAHTERAAN KELUARGA DI JAWA TIMUR - Sasongko Sasongko (EKUITAS (Jurnal Ekonomi dan Keuangan), 2010)
The purpose of this research is to examine: (1) the influence of rice for impoverished family to family’s consumption expenses; (2) the influence of rice for impoverished family to family’s socio economic condition; (3) the influence of family’s socio-economic condition to family consumption expenses; (4) the influence of family’s socio-economic condition to family welfare; (5) the influence of family’s consumption expenses to family welfare. Research variables include four latent variables and 18 indicators. The number of family samples is 180 families for Madurese culture, and 60 families for Arek culture. Based on five hypotheses proposed for each cultural area, three hypotheses are accepted for Mataraman culture, 2 hypotheses for Madurese culture, and one hypothesis for Arek culture. The research result are: (1) rice subsidy for impoverished family at Madurese culture has negative influence to family’s consumption expenses; (2) rice subsidy for impoverished family at Mataraman culture has negative influence to family’s socio-economic condition. At Madurese culture, rice subsidy gives positive influence to family’s socio-economic condition; (3) at Mataraman culture, family’s socio-economic condition has positive influence to family’s consumption expenses; and (4) family’s consumption expenses has positive influence to family welfare at Mataraman and Arek cultures.